The Effects of a Single Dialysis Session on Atrial Electromechanical Conduction Times and Functions - Hikmet Tekce; Serkan Ozturk; Gulali Aktas; Buket Kin Tekce; Alim Erdem; Mehmet Ozyasar; Tuba Taslamacıoglu Duman; Mehmet Yazici (Karger Publishers, 2013)
Background/Aims: Abnormalities in atrial electromechanical delay (EMD) times and mechanical functions are considered as independent predictors of atrial fibrillation. However, to date, effects of a single hemodialysis (HD) session and acute volume-preload changes on atrial-EMD functions have not been investigated by Tissue Doppler Echocardiography (TDE). The aim of the present study was to evaluate atrial-EMD times and mechanical functions in HD patients. Methods: Thirty-five non-diabetic, normotensive HD patients and 35 healthy control subjects were enrolled in the study. Standard and TDE performed before mid-week dialysis session for hemodialysis group and on admission for control group. Results: Interatrial and left-right intraatrial-EMD intervals and left atrial mechanical volumes were significantly longer in hemodialysis group compared to controls (all pp were independent predictors of interatrial-EMD. Conclusions: The present study confirms negative effects in HD patients of structural remodeling and reveals negative effects of electrical remodeling. Prolonged inter and intraatrial-EMD intervals should be the underlying pathophysiological factors of increased rate of atrial fibrillation in the HD population.